Engineering and design design of coastal revetments, seawalls, and bulkheads. (Dept. of the Army, Corps of Engineers, 1995)
This manual applies to HQUSACE elements, major subordinate commands, districts, laboratories, and field operating activities having civil works responsibilities.
"30 June 1995."
"This manual supercedes EM 1110-2-1614, dated 30 April 1985."
Keywords: Shore protection -- Design and construction.; Sea-walls -- Design and construction.; Bulkheads (Naval architecture) -- Design and construction.; elektronické knihy; electronic books